Using Earned Value Method in Project Control Applied research - سعيد عبد السلام لفته; فرحان خالد صبيح (Journal of Economics and Administrative Sciences, 2014)
There is no doubt that the project control function is very important for administration, so the project Management depends on to monitor and control the project. The project control integrated to the planning which is the base of the administration functions; planning, organizing, directing, and controlling. Without project control cannot be insure to fulfill the plan of the project by the budget and specified time. The project management apply many methods of control to achieve the goals of project which are cost, time, and required specifications. Earned Value Management one of control methods that used in the project by international companies. Earned Value Method is used in the project of building of Superior Judgment Council which executed by Al Mansour Company of construction contracts, long for about three years from 2010 to 2011 .Schedule of planned value, actual cost, and earned value have done to reach the control indices of Earned Value Method that are; Cost Variance, Cost Performance Index, Schedule Variance, Schedule Performance Index. Then monitor and analysis the performance of the project in aspect of cost and time ,thus the control of cost and time integrated to achieve the goals of project management .The study has reached several conclusions such as: In Al Mansour Company the cost control separated from time control of the project. The estimated cost and time have to be accurate in using Earned Value Method , and it’s important to identify the percentage of executing work accurately .So as the results of control indices would be correct.